Microstructural and Corrosion Analysis of Heat-Treated AISI 316 Stainless Steel Weldments in Acidic Environments - Adegoke Adesanmi; Ibrahim Momoh-Bello Omiogbemi; Nicholas Sylvester Gukop; Ishaya Musa Dagwa (Engineering Research: Perspectives on Recent Advances Vol. 1, 2024)
Stainless steel type AISI 316 samples were welded and subjected to post-weld heat treatment (PWHT) to analyze their microstructural and corrosion behavior. The PWHT process involved heating specific welded samples to 400°C for 12 minutes using a muffle furnace. Microstructural analysis and chemical characterization were carried out through scanning electron microscopy (SEM), while corrosion rates were determined using the weight loss method in a controlled environment. Both the as-welded and heat-treated samples were immersed in 0.5M tetraoxosulphate (IV) acid (H2SO4) at room temperature for 15 days. During this period, samples were removed every 3 days for evaluation. The results revealed that PWHT substantially improved corrosion resistance compared to the as-welded samples. This enhancement is attributed to PWHT’s role in increasing resistance to stress corrosion cracking by refining the microstructure. The research also indicated that aggressive sulphate ions (SO42-) continuously degrade the protective oxide layer on the stainless-steel surface, contributing to its corrosion susceptibility in H2SO4 environments. Additionally, two primary carbide precipitates, Cr23C6 and Cr7C3, were detected, which can negatively impact the material’s performance by promoting localized corrosion and reducing mechanical integrity. These findings emphasize the importance of PWHT in enhancing the durability and corrosion resistance of stainless steel weldments, while also highlighting the need to control carbide precipitation to ensure optimal performance in engineering and industrial applications.